Comparative study of the external auditory canal in humans and large mammals. Issue 2 (14th July 2021) - Wang, Jun; He, Aijuan; Yin, Dongming; Zhu, Yaying; Zhou, Guangdong; Zhang, Tianyu
Abstract: Given the limited source of human external auditory canal (EAC) skin, animal experiments remain an important approach for studying functional EAC reconstruction. However, differences between humans and animals in terms of the general EAC structure, histological characteristics of EAC skin, and cell markers of its specific glands in cartilaginous EAC skin remain unknown. We compared the characteristics of the EAC between humans and large animals, as a basis for appropriate animal model selection. Temporal bone computed tomography was used to compare the EACs of humans, goats, pigs, and dogs. EAC skin samples were harvested and their histological characteristics evaluated. The skin's ultrastructure and the histological structure of specific glands and cell markers related to cell phenotype and function were further identified. The EAC structure in goats was similar to that in humans in terms of diameter, length, and cartilaginous segment ratio of the EAC, while that of pigs and dogs differed markedly. Furthermore, histological evaluation showed that there were abundant ceruminous and sebaceous glands in the goat's cartilaginous skin, while dogs and pigs showed notably fewer of these glands in cartilaginous skin than humans. Nevertheless, ceruminous glands in all species studied showed similar expression of cell biomarkers and secretion function. Goats might have advantages in terms of surgery and reconstruction of the functional EAC skin compared to dogs and pigs and can be a useful candidate for ceruminous gland cell sources.